2002
DOI: 10.1364/ol.27.000809
|View full text |Cite
|
Sign up to set email alerts
|

Grating formation in pure silica-core fibers

Abstract: Strong grating formation in pure silica-core fibers by use of 193-nm ArF-laser radiation is reported. Unsaturated refractive-index changes of Dn~0.3x10(-3) were observed in nontreated fiber, and changes of Dn~0.5x10(-3) were observed in fibers with a high hydroxyl concentration. Possible mechanisms of photosensitivity in pure silica-core fibers are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 8 publications
0
40
0
Order By: Relevance
“…This result concurs with the work of Albert et. al., which showed that the loading of fibers with molecular hydrogen prior to irradiation with a UV laser at 193 nm allowed for a faster and stronger grating inscription process [13]. The lack of FL features, shown in Fig.…”
Section: Sumitomo Z-fiber (All-silica Core F-doped Cladding)mentioning
confidence: 86%
See 1 more Smart Citation
“…This result concurs with the work of Albert et. al., which showed that the loading of fibers with molecular hydrogen prior to irradiation with a UV laser at 193 nm allowed for a faster and stronger grating inscription process [13]. The lack of FL features, shown in Fig.…”
Section: Sumitomo Z-fiber (All-silica Core F-doped Cladding)mentioning
confidence: 86%
“…The repetition rate of the laser was set at 100 Hz and the pulse energy was 900 μJ. With these parameters the intensity of the laser at the fiber core was ~2x10 13 W/cm 2 , below that required for type-II damage grating formation [12]. The transmission loss at the Bragg wavelength of the grating was continuously monitored with a spectrum analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…However, such techniques are restricted to the fiber core and require a precise chemical finetuning in order to keep the guiding properties of the fiber intact. Grating formation in pristine fibers is not impossible, but comes at the expense of very long exposure times [25]. In particular fibers employed in todays high power lasers are a challenge to common inscription techniques: large core diameters, high rare-earth dopant concentration and aircladding or photoniccrystal geometries represent the most important obstacles for commercial FBG production.…”
Section: Laser and Photonics Reviews J Thomas Et Al: Femtosecond Pulsmentioning
confidence: 99%
“…However, the single material property of PCFs leads to non-photosensitivity to UV light, therefore FBGs and LPGs cannot normally be formed in PCFs by use of the conventional UV-written technique, unless a PCF with a Ge-doped photosensitive core is used [26]. Recently, several alternative methods for making LPGs in PCFs with non-photosensitive cores were introduced, including glass structure change [27], periodic structural and/ or residual stress relaxation induced by arc discharge or a CO 2 laser [28][29][30][31][32], refractive index modulation by periodically applied mechanical pressure [33] or by the use of an acoustic wave [34,35], and periodic drilling micro-holes with a femto-second laser [36].…”
Section: Fabrication Of a Pcf-lpgmentioning
confidence: 99%